Syntax der Ergaenzungsfrage Empirische Untersuchungen am Russischen, Polnischen und Tschechischen - Meyer, Roland (Slavistische Beitraege, 2004)
Questions are communicatively on an equal footing with statements. However, while the greatest number of syntactic studies deal with formal and functional aspects of declarative sentences, so far only a handful of Slavic works have been devoted to the structural features of interrogative sentences in Slavic languages. The present work shows that - contrary to the first impression - there are many relevant subtle differences in the syntax and use of supplementary questions in Slavic languages, which have to be integrated into a theory of questioning. For reviewing generalizations that v. a. Developed in formal syntax descriptions, the author uses data from extensive corpora and individual interviews as well as collected acceptability judgments from controlled experimental studies. Specifically, the work deals with Russian, Polish and Czech with the position of question expressions in simple supplementary questions, the possibilities of sentence entanglement and the syntax of questions with multiple question expressions. In addition to the surface form, the contextual and communicative function of the structure types is also taken into account.